MODEL PBL DALAM MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA SISWA - Mutmainnah Mutmainnah; Edy Nurfalah (Jurnal Riset Pembelajaran Matematika, 2019)
The purpose of this study was to describe student activities, increase learning outcomes and student responses during the learning process with PBL Model with a scientific approach to building materials for cubes, beams and prisms in class VIII D MTs Gandrirojo Sedan in 2017/2018. The subjects of this study were students of class VIII D MTs Gandrirojo Sedan totaling 34 students consisting of 18 sons and 16 girls. Data collection techniques come from students in the form of observations, tests and questionnaires. The results showed that PBL learning can improve student activity, learning outcomes and responses. This can be seen from the percentage of student activities that fall into the active category in the first cycle reaching 55.88%, the second cycle reaching 79, 41%, and the third cycle reaching 91.17%. While the percentage of mathematical learning completeness of students in the first cycle reached 61.76%, in the second cycle reached 91.17%, and in the third cycle it reached 100%. Student responses to learning are also positive. This can be seen from the results of the response questionnaire which showed that 97% of students responded positively. For this reason, learning activities using the PBL learning model can improve student activities and learning outcomes.